Factors affecting variability in free oxylipins in mammalian tissues. Issue 2 (18th March 2023) - Aukema, Harold M.; Ravandi, Amir
Abstract : Purpose of the review: Along with the growing interest in oxylipins is an increasing awareness of multiple sources of variability in oxylipin data. This review summarizes recent findings that highlight the experimental and biological sources of variation in free oxylipins. Recent findings: Experimental factors that affect oxylipin variability include different methods of euthanasia, postmortem changes, cell culture reagents, tissue processing conditions and timing, storage losses, freeze-thaw cycles, sample preparation techniques, ion suppression, matrix effects, use and availability of oxylipin standards, and postanalysis procedures. Biological factors include dietary lipids, fasting, supplemental selenium, vitamin A deficiency, dietary antioxidants and the microbiome. Overt, but also more subtle differences in health affect oxylipin levels, including during resolution of inflammation and long-term recovery from disease. Sex, genetic variation, exposure to air pollution and chemicals found in food packaging and household and personal care products, as well as many pharmaceuticals used to treat health conditions also affect oxylipin levels. Summary: Experimental sources of oxylipin variability can be minimized with proper analytical procedures and protocol standardization. Fully characterizing study parameters will help delineate biological factors of variability, which are rich sources of information that can be used to probe oxylipin mechanisms of action and to investigate their roles in health.